Carol Ann Duffy’s Everyman (2015), A Contemporary Morality Play - Esma Seçen Hınıslıoğlu (Theatre Academy)
Morality is a particular system that regulates human relations, and in this respect, moral behaviour is one of the most necessary attributes of humankind as a social being. A myriad of philosophers, writers and playwrights from various societies has tried to establish moral codes of conduct that individuals must obey in order to lead them to a better world. Emerged in the fifteenth century, morality plays still have a significant role in contemporary discussions on morality by the use of characters personifying moral qualities or abstract concepts. This review examines today’s concept of morality in Carol Ann Duffy’s Everyman (2015), an adaptation of a medieval morality play of the same name, which provides striking examples from the consumerist and materialist lifestyles of modern people.